Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1111/j.1471-4159.1983.tb12670.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anoxia on the Stimulated Release of Amino Acid Neurotransmitters in the Cerebellum In Vitro

Abstract: The effect of anoxia and ischemia on the release of amino acid transmitters from cerebellar slices induced by veratridine or high [K+] was studied. Synaptic specificity was tested by examining the tetradotoxin (TTX)-sensitive and the Ca2+-dependent components of stimulated release. Evoked release of endogenous amino acids was investigated in addition to more detailed studies on the stimulated efflux of preloaded [14C]GABA and D-[3H]aspartate (a metabolically more stable anologue of acidic amino acids). [14C]GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(47 citation statements)
references
References 35 publications
4
42
1
Order By: Relevance
“…In contrast, mammals cannot survive on anaerobic metabolism alone. Oxygen deprivation induces elevations in excitatory amino acids, which leads to overexcitation of glutamate receptors, ATP loss, anoxic depolarization, excessive Ca 2ϩ influx, and rapid excitotoxic cell death (ECD) (6,11,24,36,41). Two glutamate receptors, the N-methyl-D-aspartate receptor (NMDAR) and the ␣-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR), are the principle mediators of ECD.…”
mentioning
confidence: 99%
“…In contrast, mammals cannot survive on anaerobic metabolism alone. Oxygen deprivation induces elevations in excitatory amino acids, which leads to overexcitation of glutamate receptors, ATP loss, anoxic depolarization, excessive Ca 2ϩ influx, and rapid excitotoxic cell death (ECD) (6,11,24,36,41). Two glutamate receptors, the N-methyl-D-aspartate receptor (NMDAR) and the ␣-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR), are the principle mediators of ECD.…”
mentioning
confidence: 99%
“…Increased release of excitatory amino acids has been reported during cerebral ischemia in vivo 12 " 15 and during simulated ischemic conditions in vitro. 16 " 18 A number of in vitro and in vivo experimental studies have shown that excitatory amino acid receptor antagonists have a protective effect on brain following cerebral ischemia. 19 -28 One putative source of oxygen free radicals during cerebral ischemia is the arachidonic acid cascade.…”
mentioning
confidence: 99%
“…In the present study, we compared changes in the concentrations of other EAA neurotransmitters and nontransmitter amino acids with CBF decreases and electrophysiologic impairment. [1], costocervical trunk [2], superficial cervical artery [3], and internal thoracic artery [4]) through transverse skin incision along upper margins of pectoral muscles in cat.…”
mentioning
confidence: 99%